Professional training of masters in music therapy at Universities of the USA - Li, Shanyin (Національний університет «Львівська політехніка», 2024)
Research topicality. The 21st century is characterized not only by significant achievements in the development of science, but also by growing problems related to the health of the population, both mental and physical. This situation encourages the development and implementation of new methods of treatment and rehabilitation that can be effective for different segments of the population. Music Therapy is one of those methods that involve the use of musical interventions for therapeutic purposes. The use of music helps clients to improve their emotional state, increase the level of social adaptation, and maintain cognitive and physical functions. Music Therapy includes various techniques such as musical improvisation, listening to music, writing songs, analysing lyrics, singing and moving to music. In a therapeutic context, it can complement both psychotherapy and physiotherapy, being an effective tool in working with different groups of clients, from children to the elderly. Актуальність дослідження. 21 століття характеризується не тільки значними досягненнями у розвитку науки, але й зростаючими проблемами, що стосуються здоров’я населення, як психічного, так і фізичного. Така ситуація спонукає до розробки та впровадження нових методів лікування та реабілітації, які можуть бути ефективними для різних верств населення. Музична терапія є одним із тих методів, які передбачають використання музичних інтервенцій з терапевтичною метою. Застосування музики допомагає пацієнтам покращувати емоційний стан, підвищувати рівень соціальної адаптації, підтримувати когнітивні та фізичні функції. Музична терапія включає різні техніки, такі як музичні імпровізації, слухання музики, написання пісень, аналіз текстів пісень, спів та рух під музику. У лікувальному контексті вона може доповнювати як психотерапію, так і фізіотерапію, будучи ефективним інструментом у роботі з різними групами пацієнтів, від дітей до людей похилого віку.
Професійна підготовка магістрів з музичної терапії в університетах США
Keywords: Music Therapy, music therapist, master’s degree, university, educational program, USA, Ukraine, health care, theoretical training, practical training, knowledge, abilities and skills, competences, organizational forms of training, interactive teaching methods, музична терапія, музичний терапевт, магістр, університет, освітня програма, США, Україна, охорона здоров’я, теоретична підготовка, практична підготовка, знання, уміння і навички, компетентності, організаційні форми навчання, інтерактивні методи навчання; 378.4:78](073)(043.5)